2013
DOI: 10.1371/journal.pone.0053043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Influence of Enterococcus faecium on the Propagation of Swine Influenza A Virus In Vitro

Abstract: The control of infectious diseases such as swine influenza viruses (SwIV) plays an important role in food production both from the animal health and from the public health point of view. Probiotic microorganisms and other health improving food supplements have been given increasing attention in recent years, but, no information on the effects of probiotics on swine influenza virus is available. Here we address this question by assessing the inhibitory potential of the probiotic Enterococcus faecium NCIMB 10415… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…E. faecium was shown to increase cell survivability (40-80%) and reduce viral titers (up to 4 log) of both SwIV strains in two media [59]. In this publication, it was hypothesized and demonstrated that E. faecium operates through the adsorption of viral particles as well as the stimulation of nitric oxide production, which in itself has antiviral properties.…”
Section: Swinementioning
confidence: 97%
See 1 more Smart Citation
“…E. faecium was shown to increase cell survivability (40-80%) and reduce viral titers (up to 4 log) of both SwIV strains in two media [59]. In this publication, it was hypothesized and demonstrated that E. faecium operates through the adsorption of viral particles as well as the stimulation of nitric oxide production, which in itself has antiviral properties.…”
Section: Swinementioning
confidence: 97%
“…Enterococcus faecium NCIMB 10415 is a recognized probiotic approved by the European Union and has been evaluated for its efficacy in reducing swine influenza virus (SwIV), specifically H1N1 and H3N2 [59]. E. faecium was shown to increase cell survivability (40-80%) and reduce viral titers (up to 4 log) of both SwIV strains in two media [59].…”
Section: Swinementioning
confidence: 99%
“…21 The probiotic form of E. faecium (NCIMB 10415) also increased the production of NO by the phagocyte cells of pigs. 22 Based on the results, it appears that E. faecium modulates the innate immunity to fight against pathogens.…”
Section: Enterococcus Faecium and Its Effects On The Immune Responsesmentioning
confidence: 99%
“…Function of jejunum epithelium 17 T 10 Jejunum gene expression 7 T 11 Jejunum morphology 3 T 12 Intestinal microbial metabolites in stomach digesta…”
Section: Enrichment Analysismentioning
confidence: 99%
“…In vitro experiments with porcine cell cultures have indicated a protective potential against virus infections. [11,12] Moreover, a previous feeding trial identified alterations of intestinal bacterial communities and immune parameters as a reaction to the supplementation of E. faecium NCIMB 10415 to growing piglets. [13] Results from another feeding trial with E. faecium NCIMB 10415 revealed a broad spectrum of effects: increased absorptive and secretory transport capacities, [14] improved intestinal barrier function of jejunum epithelia, [14] a reduced feed conversion ratio, [15] activation of cytotoxic T-cells, [16] but a lack of protection against Salmonella infection, [17] an altered occurrence of pathogenic genes in intestinal Escherichia coli (E. coli) populations [18] and altered expressions of cytokines.…”
Section: Introductionmentioning
confidence: 99%